Taylor Visits Africa - Goncalves, Carlos (IMF Working Papers; Working Paper, 2015)
Many low-income countries do not use interest rates as their main monetary policy instrument. In East Africa, for instance, targeting money aggregates has been pretty much the rule rather than the exception. Nevertheless, these targets are seldom met and often readjusted according to the economic environment. This opens up the possibility that central banks are de facto pursuing a strategy more akin to a Taylor Rule. Estimations of small-scale models for Kenya, Uganda and Tanzania suggest that these self-styled "monetary targeters" are respecting the Taylor Principle, that is are on average increasing nominal interest rates more than proportionally to inflation. Nevertheless, steep deviations from the Taylor Rule have taken place in Kenya and Tanzania. In Uganda, these errors are much smaller, in fact similar in size to Taylor Rule deviations found for Brazil. More surprisingly, they are smaller than South Africa's, the continent's sole long-term inflation targeter.